Mapaz: population and environment web mapping for the sustainable Amazon - International Center for Tropical Agriculture; World Agroforestry Centre; Center for International Forestry Research; Amazon Initiative Consortium (2011)
Mapaz helps policymakers and scientists target research and development or conservation activities in the Amazon by pulling together information on elements such as deforestation, biomass, species diversity, population, poverty and regional land use. Users can define their own geographic areas or select existing administrative boundaries to get spatial information for that area in the form of maps and tables. For example, MAPAZ calculates biomass,